Strategi Pemberdayaan Komunitas Lokal: Menuju Kemandirian Daerah - Trijono, Lambang (Jurnal Ilmu Sosial dan Ilmu Politik, 2001)
Rhetorically, local authonomy and societal empowerment are mutually required. The lacking of structural and political understanding of the notion of empowernment has allowed the sustenance of status quo.